"B?BURN?MA"DA QO‘LLANILGAN MAQOLLARNING USLUBIY ?USUSIYATLARI - Masharipova Umidaxon Xudoyberganovna; MARIFOVNA, Kenjaev Farxod (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
The article gives a review on the thematic lexical-semantic classification of some lexical units, as well as on Babur’s verbal skills, his ability to methodologically use folk proverbs